Polymers in Modern Medicine - Part 2 - Namdeo Kothawade, Sachin; Vijay Pande, Vishal (Bentham Science Publishers, 2024)
Polymers in Modern Medicine – Part 2 examines the innovative use of polymers in advanced healthcare applications, focusing on personalized medicine, regenerative therapies, and diagnostics. The book highlights groundbreaking topics such as polymer-based nanomedicine for cancer therapy, polymeric hydrogels, biopolymers, and the role of polymers in diagnostics and vaccines. Building on foundational principles, it explores polymeric approaches to sustainable and patient-specific treatments.Readers will gain a deep understanding of emerging polymer technologies and biocompatible materials and their impact on cutting-edge medical solutions. This resource bridges the gap between scientific research and practical implementation in the pharmaceutical, biomaterial, and medical device industries.Key Features:- Covers polymers in regenerative medicine, nanomedicine, and diagnostics.- Insights into polymeric hydrogels, biopolymers, and smart polymers.- Sustainability and patient-specific applications in healthcare.